Indigenous Tocopherol Improves Tolerance of Oilseed Rape to Cadmium Stress - Ali, Essa; Hassan, Zeshan; Irfan, Muhammad; Hussain, Shabir; Rehman, Haseeb-ur-; Shah, Jawad Munawar; Shahzad, Ahmad Naeem; Ali, Murtaza; Alkahtani, Saad; Abdel-Daim, Mohamed M.; Bukhari, Syed Asad Hussain; Ali, Shafaqat (Frontiers in Plant Science, 2020)
Two oilseed rape genotypes (Jiu-Er-13XI and Zheyou-50), differing in seed oil contents, were subjected to Cd stress in hydroponic experiment. Genotypic differences were observed in terms of tolerance behavior towards Cd exposure. Cd treatment negatively affected both genotypes but the effects were more prominent in Jiu-Er-13XI (low seed oil content) as compared to the Zheyou-50 (high seed oil content). Jiu-Er-13XI accumulated more reactive oxygen species (ROS), which destroyed chloroplast structure and decreased photosynthetic pigments. Total fatty acids, especially 18:2 and 18:3, were severely decreased as suggested by increase in MDA contents. Jiu-Er-13XI accumulated more Cd in its roots and shoots while less amount of tocopherol was observed under Cd stress. In contrast, Zheyou-50 was less affected by Cd stress than its counterpart. It accumulated comparatively less amount of Cd in roots and shoots, along with reduced accumulation of malondialdehyde (MDA) and ROS under Cd stress, than Jiu-Er-13XI. In addition the level of tocopherol, especially the α-Tocopherol, was much higher than Jiu-Er-13XI, which was also supported by high expression of tocopherol biosynthesis genes in Zheyou-50 during early hours. Tocopherol not only restricted the absorption of Cd by roots and its translocation to shoot, but also scavenged the ROS, generated during oxidative stresses. The low level of MDA shows that polyunsaturated fatty acids in chloroplast membranes were intact. In present study the tolerance behavior of Zheyou-50 over Jiu-Er-13XI is attributed to the activities of tocopherol under Cd stress. This study shows that plants with high seed oil are tolerant to Cd stress due to high production of tocopherol.